2022-RA-955-ESGO Endometrial cancer: lymphovascular space invasion is a negative prognostic factor. (20th October 2022) - Salmon, Alixe; Dheur, Adriane; Bours, Vincent; Delbecque, Katty; Gonne, Elodie; Pleyers, Clemence; de Cuypere, Marjolein; Goffin, Frederic; Lovinfosse, Pierre; Kridelka, Frederic; Kakkos, Athanasios; Gennigens, Christine
Abstract : Introduction/Background: Endometrial carcinoma (EC) is the most common cancer of the female genital tract in developed countries. Lymphovascular space invasion (LVSI), an histological characteristic, is also included in the molecular classification. We aimed to compare the clinical profile but also overall survival (OS) and progression-free survival (PFS) in patients with and without LVSI. Methodology: Between January 2019 and December 2021, we conducted a monocentric retrospective study of 166 patients treated for EC (all stages) at the CHU of Liège. Thirty-nine patients were excluded. Data of the 127 remaining patients were analyzed for quantification of LVSI: absence, rare (< 5), substantial (≥ 5) or lymphangitis. The statistical correlation between the LVSI status and various clinical (FIGO stage, lymph node invasion, histological type and grade) and molecular factors was assessed using chi-square and Fisher's exact tests. Kaplan-Meier methods were used to determine OS and PFS. Results: 33.6% ( n = 37/127) – 40.9% ( n = 45/127) – 21.8% ( n = 24/127) and 3.6% ( n = 4/127) have absence, rare, substantial LVSI and lymphangitis, respectively. There is a significant correlation between the presence of LVSI (LVSI+) and higher grade (p=0.0001) but also with lymph node invasion (12.2% vs 0%, p=0.046). OS at 24 months was 96% and 82% in LVSI – and LVSI + cohorts, respectively (HR = 2.59, p=0.37). Regarding molecular analyses, more patients with LVSI+ have microsatellite instability (42.7% vs 16.2%, p=0.0045). No significant correlation was found between the LVSI quantification and p53 mutation, POLE status or histological subtype. Conclusion: The presence of LVSI is a negative prognostic factor, with aggressive features, but without statistically reduction in OS. However, concerning absolute values, the presence of LVSI demonstrates worse prognosis. A significant association with microsatellite instability is demonstrated. The LVSI status should systematically be determined to optimally define the patient prognosis.